2019
DOI: 10.3389/fmicb.2019.00742
|View full text |Cite
|
Sign up to set email alerts
|

Temperate Prophages Increase Bacterial Adhesin Expression and Virulence in an Experimental Model of Endocarditis Due to Staphylococcus aureus From the CC398 Lineage

Abstract: Until 2007, Staphylococcus aureus from clonal complex 398 (CC398) was exclusively associated with livestock species and companion animals. Recently, several studies described the emergence of S. aureus CC398 as etiologies of severe infections in humans living in an animal-free environment. Recent sequencing efforts showed that the mobile genetic elements found in CC398 isolates were specific for each population and enabled differentiation of strains responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
1
18
0
4
Order By: Relevance
“…In Staphylococcus aureus , a closely related species to S . epidermidis , prophages increase virulence of their bacterial host, most probably by promoting interaction with extracellular matrix components or by integration of phage-encoded virulence determinants into the staphylococcal genome [ 75 , 76 ]. Future studies will therefore need to address whether prophages may at least partly explain the over-representation of ST2 in S .…”
Section: Discussionmentioning
confidence: 99%
“…In Staphylococcus aureus , a closely related species to S . epidermidis , prophages increase virulence of their bacterial host, most probably by promoting interaction with extracellular matrix components or by integration of phage-encoded virulence determinants into the staphylococcal genome [ 75 , 76 ]. Future studies will therefore need to address whether prophages may at least partly explain the over-representation of ST2 in S .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human SA CC398 had a higher capacity for binding to human cytokeratin-10 than LA SA CC398, mediated by the clumping factor B (ClfB) and very likely important for nasal colonization of humans [9]. Recently, Laumay and colleagues showed that the introduction of bacteriophages from the genomes of human-adapted SA to that of a naive SA animal colonizer increased the transcription of clfA (encoding the clumping factor A precursor) and fnbA (encoding the fibronectin binding protein), which in turn increased the bacterial virulence in a rat model of infectious endocarditis [89]. This study confirmed the role of MGE in the virulence of SA CC398.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…An increase in the production of virulence factors was observed, which could not be attributed to insertional effects. Hence, it is tempting to hypothesize that those phages carry uncharacterized regulators influencing the expression of bacterial adhesins and so increase the ability to adhere to human extracellular matrix proteins 79 .…”
Section: Prophages Impact Bacterial Infectivitymentioning
confidence: 99%